Metode Penelitian Kualitatif Studi Pustaka - Miza Nina Adlini; Anisya Hanifa Dinda; Sarah Yulinda; Octavia Chotimah; Sauda Julia Merliyana (Universitas Muhammadiyah Enrekang, 2022)
This study aims to discuss qualitative research methods literature study. The method used is literature study, data collection by searching for sources and constructing from various sources such as books, journals, and existing research. As a result, qualitative research was carried out with a research design whose findings were not obtained through procedures or in the form of calculations, but revealed a holistic-contextual phenomenon by collecting data from researchers in natural settings/settings and using it as a key instrument. Qualitative research has a descriptive nature and tends to use an inductive approach to analysis, so that the process and meaning based on the subject's perspective are highlighted in this qualitative research. This qualitative research design can be used as a method in research, because it is a comprehensive design that is easily accessible by academic circles and researchers.